Analisis Kadar Logam Besi (Fe) pada Depot Air Minum Isi Ulang di Kota Lhokseumawe - Atika Fadhilla; Cut Khairunnisa; Yuziani Yuziani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Drinking water is a very important component in everyday life. Refill Drinking Water Depot (DAMIU) is a business that produces drinking water so that it can be consumed directly by the public. The quality of refill drinking water must be considered because it can be contaminated by heavy metals from the environment or due to negligence of human activities. Excessive iron (Fe) in drinking water can be toxic and endanger health. Excess Fe intake for a long time will result in secondary hemochromatosis and dental caries. This study was conducted to determine the content and average levels of Fe contained in 51 samples of DAMIU in Lhokseumawe City. This type of research is descriptive laboratory. The sampling technique used in this research is simple random sampling. Fe levels were measured using Atomic Absorption Specthrophotometry through the SSA-Flame method and the results were based on the PERMENKES RI No. 492/MENKES/PER/IV/2010 with the provision that Fe content should not exceed 0.3 mg/L. The results of this study indicate that the average Fe level in refill drinking water depots in Lhokseumawe City is 0.243 mg/L which is still below the predetermined threshold, but from 51 samples, 16 samples exceeded the threshold and 35 samples did not exceed the threshold. This study can be concluded that there are 31% of the tested drinking water samples have Fe levels that exceed the specified threshold.